2019
DOI: 10.1002/adsc.201801371
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Enantioselective Metal‐Catalyzed Domino Reactions

Abstract: This review collects the very recent developments in enantioselective metal-catalyzed domino reactions published since the beginning of 2016. It illustrates that many types of enantioselective metal-catalyzed domino processes continue to be developed, allowing an easy one-pot access to complex molecular architectures from simple starting materials taking economic advantages, such as avoiding costly protecting groups and timeconsuming purification procedures after each step. 1 Introduction 2 Enantioselective Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 98 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…We found that both halogenated alkane and triethylamine hadt he same quenching effect on the photosensitizer,b ut the quenching coefficient of halogenated alkane (K SV (ICF 2 CO 2 Et), 0.6 mm À1 ) was much larger than that of triethylamine (K SV (Et 3 N), 0.05 mm À1 ), so halogenated hydrocarbon might be the major quenching agent.Ar eaction quantum yield was measured to be f= 3.2%,i ndicating the radicalc hain mechanism is less likely.B ased on above results, ap lausible mechanism is outlined in Figure 1. Photoexcitationo f[ Ru(bpy) 3 Cl 2 ]·6H 2 Ou pon blue irradiation resultsi nametal-to-ligand charge transfer (MLCT) exciteds tate. [11] Then difluoroalkyl radicali sg enerated througho xidative quenching.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We found that both halogenated alkane and triethylamine hadt he same quenching effect on the photosensitizer,b ut the quenching coefficient of halogenated alkane (K SV (ICF 2 CO 2 Et), 0.6 mm À1 ) was much larger than that of triethylamine (K SV (Et 3 N), 0.05 mm À1 ), so halogenated hydrocarbon might be the major quenching agent.Ar eaction quantum yield was measured to be f= 3.2%,i ndicating the radicalc hain mechanism is less likely.B ased on above results, ap lausible mechanism is outlined in Figure 1. Photoexcitationo f[ Ru(bpy) 3 Cl 2 ]·6H 2 Ou pon blue irradiation resultsi nametal-to-ligand charge transfer (MLCT) exciteds tate. [11] Then difluoroalkyl radicali sg enerated througho xidative quenching.…”
mentioning
confidence: 99%
“…[2] In this regard, transition-metal-catalyzed multicomponent reactions prove to be an ideal technology.A voidingt he synthesis of starting material, in as ingle operation, severaln ew bonds are formed and new functionalities are introduced. [3] In the meantime,i ncorporation of fluorinea toms into organic motifs has asignificant influence on the lipophilicity,metabolic stability, and bioavailability of organic molecules. [4] Fluoroalkylation using relativelym ild fluoroalkylh alides as af luorine source has been the focus of current research.…”
mentioning
confidence: 99%
See 3 more Smart Citations